Patterns of Level and Change in Self-Reported Driving Behaviors Among Older Adults: Who Self-Regulates? - O’Connor, Melissa L. (Oxford University Press, 2012)
OBJECTIVES. The present study investigated patterns of self-reported driving habits among healthy older adults over 5 years, as well as characteristics that distinguished subgroups with different patterns. METHODS. Participants were drivers from the control group of the Advanced Cognitive Training for Independent and Vital Elderly study at the baseline assessment (N = 597). The outcome was a composite of driving frequency, driving space, and perceived driving difficulty. Growth mixture models identified classes of participants with different baseline scores and change trajectories, and classes were compared in terms of baseline sensory, physical, and cognitive functioning. RESULTS. A 3-class model was indicated, consisting of 2 classes with intercept differences and stability over time, “above-average stable” (39%) and “average stable” drivers (44%), and 1 class with a lower intercept and negative slope, “decreasers” (17%). Relative to stable drivers, decreasers exhibited significantly more depressive symptoms and poorer self-rated health, balance, everyday functioning, and speed of processing after controlling for age and education (p < .05). DISCUSSION. The majority of older drivers maintained their driving over time at different levels, whereas a subgroup of individuals with poorer baseline functioning self-regulated by reducing their driving. Future studies should determine how such patterns affect driving safety.